2008
DOI: 10.1074/jbc.m706854200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Francisella tularensis Lipoproteins That Stimulate the Toll-like Receptor (TLR) 2/TLR1 Heterodimer

Abstract: The innate immune response to Francisella tularensis is primarily mediated by TLR2, though the bacterial products that stimulate this receptor remain unknown. Here we report the identification of two Francisella lipoproteins, TUL4 and FTT1103, which activate TLR2. We demonstrate that TUL4 and FTT1103 stimulate chemokine production in human and mouse cells in a TLR2-dependent way. Using an assay that relies on chimeric TLR proteins, we show that TUL4 and FTT1103 stimulate exclusively the TLR2/TLR1 heterodimer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 41 publications
2
92
0
Order By: Relevance
“…holarctica reacting with human tularemic sera. Interestingly, the glycosylated lipoproteins FTH_1071 and FTH_0414 were also previously found to interact with TLR-2/ TLR-1 heterodimers of HeLa cell lines, resulting in the induction of a proinflammatory response (512). Since interaction with these TLRs is generally mediated via acylation, glycosylation is thought to play a modulatory role, as shown by Sieling et al (513).…”
Section: Protein Glycosylationmentioning
confidence: 90%
“…holarctica reacting with human tularemic sera. Interestingly, the glycosylated lipoproteins FTH_1071 and FTH_0414 were also previously found to interact with TLR-2/ TLR-1 heterodimers of HeLa cell lines, resulting in the induction of a proinflammatory response (512). Since interaction with these TLRs is generally mediated via acylation, glycosylation is thought to play a modulatory role, as shown by Sieling et al (513).…”
Section: Protein Glycosylationmentioning
confidence: 90%
“…TLR2 is the primary TLR involved in the inflammatory response to Francisella infection (1). Known Francisella TLR2 agonists include the uncharacterized lipoproteins LpnA/Tul4 and FTT_1103 (86,220). To our knowledge, TLR2 recognition of Francisella PGN has not been reported, and the status of PGN as a TLR2 ligand is still under debate (12,73,222).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…4C), we concluded that our recombinant proteins were not contaminated with TLR2 ligands. To further conclusively demonstrate that the proinflammatory effects of LukS and PVL depended on the proteins and not contaminating lipoproteins, we stimulated MH-S cells with LukS, PVL, and the lipoprotein Pam 3 CSK 4 in their native forms or after treatment with proteinase K or NaOH, which is known to hydrolyze the N-terminal acyl chains of bacterial lipoproteins (38). As shown in Supplemental Fig.…”
Section: Pvl Activates Transcription Of a Small Subset Of Nf-kb-regulmentioning
confidence: 99%